The Makkan Show: The Triumph of Korean Entertainment Theater (Taejung-gŭk) of the 1930s (Politeja, 2025)
The research subject of the article is the ‘makkan show’ (makkan-gŭk). It developed in the early 1930s as an integral part of Korean entertainment theater (taejung-gŭk). Initially, it included simple vocal songs and dialogue scenes presented by actors between different plays. As its popularity grew, it transformed into an autonomous show that combined vocal and dance performances, popular Western music, film, and most importantly, improvised satirical scenes, presented either solo or in duets. The ‘makkan show’ dominated the program of many taejung-gŭk companies and became a symbol of taejung-gŭk theater. The primary purpose of this article is to describe the ‘makkan show,’ explain the reasons of its popularity, and try to answer the question of whether its function was limited solely to entertainment purposes.